Militâncias : andarilhando por territórios de vida - Vitor Júnior, Antônio Martins (2015)
In this research we propose to problematize the militancy. Therefore, we shall lay hold of discussions about the ways of production of subjectivity and of life. This work is organized like a dissertation-compass, being sustained by trips throughout Latin America. The acting alongside the population in street situation, through the Projeto Andarilhos in Brazil, triggered the interest in a research rested in the encounters with movements for the legalizations of marijuana, of abortion and of equal marriage in Uruguay; for the struggles for free and public education in Chile and with the zapatista movements in Mexico. The choice for traveling takes place on the basis of strategic action towards the production of connections and alliances with movements that contribute with the denaturalization of certain practices of militancy. In this work, the image of the wanderer as opposed to the tourist, in light of the geographic and magnetic norths, is important subside for the discussion of the ways of traveling and exercising militancy. The objective is to produce encounters and to narrate stories arisen in the route of wandering through territories of life. Militancy, thus, emerges from the affirmation of life produced in the encounters by the wandering.